Political Communication and Personal Imaging (Study of Giring Ganesha’s Political Speech at Indonesian Solidarity Party Anniversary) - Markus Utomo Sukendar (Universitas Muhammadiyah Surakarta, 2023)
Speech delivery is a form of communication skill that aims to convey certain messages to the public. In giving speeches or giving speeches, especially in political speeches, a political party figure carries out the duties and carries out the functions of his party. The purpose of the research is to dissect the communication message conveyed by Giring Ganesha as the general chairman of PSI in the Political Speech at PSI's 7th Anniversary, as well as to find out the purpose of Giring Ganesha as a representation of PSI and the impression that is built as part of political imagery.Â This research is a qualitative exploratory research, which is used to explore data so that it can provide in-depth understanding and understanding of the object of research. This study is directed to clearly describe the image formed by Giring Ganesha who is also the General Chair of the Indonesian Solidarity Party in his political speech for the 7th Anniversary of the Indonesian Solidarity Party on December 22, 2021. The research method used in this study is discourse analysis by Roger Fowler et al. According to Focault, discourse is a field of all statements, sometimes as an individualization of a group of statements, and sometimes as a regulatory practice seen from a number of statements. (1) Giring Ganesha's speech as a party representative further strengthens PSI's support for President Joko Widodo's Government and it is recognized that President Jokowi's magnetism is still very strong in gaining constituent support, especially young people. (2) As a form of modern, adaptive, intoxicated Party image.